Speak American : a survival guide to the language and culture of the U.S.A. - Johnston, Dileri Borunda (New York : Random House, 2002)
A reference guide to the language and culture of the United States for people from other countries who are visiting or doing business in America.
Maps on inside cover.
Adult
Keywords: Americanisms; English language -- Textbooks for foreign speakers; English language -- Spoken English -- United States; English language -- United States -- Conversation and phrase books; Americanisms; English as a second language; English language -- United States; English language -- United States -- Conversation and phrase books